Experience into fiction: Israeli writers on Jewish-Arab relations - Shaked, Haim (In:The Contemporary Middle Eastern scene;Opladen : Leske + u. Budrich, 1979;(1979), Seite 138-149;192 Seiten, 1979)
Aus israelischer Sicht
Keywords: Bevölkerung; Sozialverhalten; Literatur; Zensur